Amyloid Imaging in Aging and Dementia: Testing the Amyloid Hypothesis In Vivo - G. D. Rabinovici; W. J. Jagust (Behavioural Neurology, 2009)
Amyloid imaging represents a major advance in neuroscience, enabling the detection and quantification of pathologic protein aggregations in the brain. In this review we survey current amyloid imaging techniques, focusing on positron emission tomography (PET) with ^{11}carbon-labelled Pittsburgh Compound-B (11C-PIB), the most extensively studied and best validated tracer. PIB binds specifically to fibrillar beta-amyloid (Aβ) deposits, and is a sensitive marker for Aβ pathology in cognitively normal older individuals and patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD). PIB-PET provides us with a powerful tool to examine in vivo the relationship between amyloid deposition, clinical symptoms, and structural and functional brain changes in the continuum between normal aging and AD. Amyloid imaging studies support a model in which amyloid deposition is an early event on the path to dementia, beginning insidiously in cognitively normal individuals, and accompanied by subtle cognitive decline and functional and structural brain changes suggestive of incipient AD. As patients progress to dementia, clinical decline and neurodegeneration accelerate and proceed independently of amyloid accumulation. In the future, amyloid imaging is likely to supplement clinical evaluation in selecting patients for anti-amyloid therapies, while MRI and FDG-PET may be more appropriate markers of clinical progression.